2020
DOI: 10.1186/s12964-020-00631-9
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured regions of large enzymatic complexes control the availability of metabolites with signaling functions

Abstract: Metabolites produced via traditional biochemical processes affect intracellular communication, inflammation, and malignancy. Unexpectedly, acetyl-CoA, α-ketoglutarate and palmitic acid, which are chemical species of reactions catalyzed by highly abundant, gigantic enzymatic complexes, dubbed as “metabolons”, have broad “nonmetabolic” signaling functions. Conserved unstructured regions within metabolons determine the yield of these metabolites. Unstructured regions tether functional protein domains, act as spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 81 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…In addition, multiple cryo-EM reconstructions have shown that observing numerous, large-scale conformational variations among structural states is possible (Saibil, 2000), e.g., during elongation in protein translation (Behrmann et al, 2015) or breathing motions of purified fatty acid synthase (Ciccarelli et al, 2013). Disordered regions of proteins in particular can now be better understood in the context of the metabolons (Skalidis et al, 2020), and advances in cryo-EM image processing methods may even allow their direct visualization (Punjani and Fleet, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, multiple cryo-EM reconstructions have shown that observing numerous, large-scale conformational variations among structural states is possible (Saibil, 2000), e.g., during elongation in protein translation (Behrmann et al, 2015) or breathing motions of purified fatty acid synthase (Ciccarelli et al, 2013). Disordered regions of proteins in particular can now be better understood in the context of the metabolons (Skalidis et al, 2020), and advances in cryo-EM image processing methods may even allow their direct visualization (Punjani and Fleet, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has become evident that, in the proteome, a relatively large protein fraction in eukaryotes (bioinformatics prediction is up to 30% of IDRs) lacks partially defined and stable secondary or tertiary structures. These IDPs and IDRs display highly dynamic ensembles of multiple conformations. IDPs often fulfill key roles in many cellular functions, including signal transduction, , control of enzymatic activity, and transcription where conformational plasticity confers a number of advantages. At the same time, the inherent flexibility of IDPs presents major challenges to 3D-structural studies that employ classical biophysical approaches. ,,, Despite the fact that very little is known about their structure-dependent mechanisms of action, IDPs and IDRs are often associated with disease states, thus rendering them attractive drug targets. This underlines the importance of investigating dynamic conformational ensembles, potential structural transitions, potentially extant post-translational modifications (PTMs), and transient and low-affinity interactions that govern the regulatory functions of IDPs. ,, Such a broad spectrum of structural information can only be addressed by integrating a variety of methodological approaches to fully understand the structures, dynamics, and interactions of IDPs.…”
Section: Xl-ms For Addressing Specific Biological Systemsmentioning
confidence: 99%
“…Recent studies not only increased the achievable resolution (Arimura et al, 2020;Ho et al, 2020;Su et al, 2021), particularly in the membrane (Su et al, 2021) or nuclear extracts (Arimura et al, 2020) but also determined the snapshots of higher-order organization of in-extract flexible, functional metabolons (Kyrilis et al, 2021). The importance and challenges of integrative structural studies of native extracts and the correlation between structural disorder and function for inextract metabolons were recently reviewed (Kyrilis et al, 2019;McCafferty et al, 2020;Skalidis et al, 2020). Reaching the milestone of near-atomic detail a few years ago proved that native cell extracts are amenable to structural studies and considerably broadened the structural proteomics field by expanding the concept of "protein communities" (Kastritis et al, 2017), primarily described by Gavin et al (2006).…”
Section: Introductionmentioning
confidence: 99%